Hydrodynamic Forces on Linear and Multi-Dimensional Arrays of Circular Cylinders - Sebastian, A.A. (2014)
In this paper, major focus is given for determining the accurate wave forces recorded on circular cylinders present in different array configurations. Investigation is made to establish any trend in variation of these forces, when the wave time periods, location of the cylinders in the array and the spacing between cylinders are varied. Wave tank model tests were conducted in regular waves. Tandem cylinder configurations involving a maximum of four cylinders were considered for the present study. In addition to this, two linear arrays of four cylinders each, were installed side by side in the waves and the forces on each of the cylinders were determined. The spacing between the cylinders in this two dimensional array was varied and the trend in the variation of forces are presented. Change of transverse spacing between the cylinders was found to have more effect on the forces on cylinders, than the change in in-line spacing. The wave forces acting on singly existing cylinders were found to be less than that acting on individual cylinders present in the different array configurations considered. The variation of drag coefficients with respect to the time periods was found to be of random nature. Morison equation is made use in the determination of drag coefficients.